The influence of different screw tightening forces on the vertical misfit of implant-supported frameworks Avaliação do efeito da força de aperto de parafusos de retenção na desadaptação marginal de próteses sobre implantes - Diego Klee de Vasconcellos; Marco Antonio Bottino; Renato Sussumu Nishioka; Luiz Felipe Valandro; Elza Maria Valadares da Costa (Journal of Applied Oral Science, 2005)
OBJECTIVES: The present in vitro study was designed to compare the differences in the vertical misfit of implant-supported frameworks using three different forces for tightening the bridge locking screws: fastening by hand until first resistance, and using torque drivers with 10 and 20Ncm. METHODS: The investigation was conducted based on the results given by 9 six-unit nickel-chromium (2 abutments/ 4 pontics) screw-retained implant-supported frameworks. The structures were exposed to simulated porcelain firings. The marginal misfit measurements were made using a traveling measuring microscope at selected screw tightening forces: fastening by hand until first resistance, and using torque drivers with 10 and 20Ncm. The results were submitted to one-way ANOVA with repeated measures on one factor, and post hoc pairwise comparisons using Tukey test (5%). RESULTS: The mean marginal misfit of the frameworks, fastening the screws by hand until first resistance, was 41.56µm (SD±12.45µm). The use of torque driver devices caused a significant reduction in marginal opening (p<0.05). With the lowest torque available (10Ncm), the mean marginal discrepancy at the abutment-framework interface was reduced an average of 52% to a mean marginal opening of 19.71µm (SD±2.97µm). After the use of the 20Ncm torque driver, the mean marginal discrepancy of the frameworks was reduced an average of 69% to a mean marginal opening of 12.82µm (SD±4.0µm). Comparing the use of torque drivers with 10 and 20 Ncm torque, the means are not significantly different from one another. CONCLUSION: The seating force has an important effect on the vertical misfit measurements, once it may considerably narrow the vertical misfit gaps at the abutment-framework interface, thus leading to a misjudgment of the real marginal situation. O presente estudo avaliou o efeito da força de aperto de parafusos de retenção na desadaptação marginal de próteses sobre implantes. A investigação foi conduzida baseada em resultados fornecidos por nove estruturas metálicas implanto-suportadas de seis elementos (02 retentores e 04 pônticos), retidas por parafusos. A mensuração da desadaptação marginal foi realizada com auxílio de microscópio óptico, nos seguintes momentos: M1: aperto com chave manual até a primeira resistência do parafuso; M2: aperto utilizando torquímetro mecânico com 10Ncm e M3: aperto utilizando torquímetro mecânico com 20Ncm. As médias de desadaptação foram submetidas à análise estatística (ANOVA e Tukey). O emprego de torquímetros mecânicos, independente do valor de torque, determinou redução significativa na abertura marginal (p<0,05). A desadaptação média na interface conexão/prótese em M1 foi de 41,56µm (DP±12,45µm). O emprego do torquímetro de 10Ncm (M2), reduziu 52% desta fenda marginal, para uma média de desadaptação de 19,71µm (DP±2,97µm); enquanto o torquímetro de 20Ncm (M3) reduziu 69% da desadaptação marginal, para uma média de 12,82µm (DP±4,0µm) os de retenção de próteses implanto-suportadas tem importante efeito na mensuração da desadaptação marginal, uma vez que pode modificar consideravelmente as aberturas na interface conexão/prótese.